Deep Vein Thrombosis Related with Henoch-Schönlein Purpura in Pediatric Patient - Srithanetsakul, Sirada; Nilrod, Burawat (Thai Journal of Dermatology, 2024)
Henoch-Schönlein Purpura is a condition within the vasculitis groups. It can result in manifestations, including abdominal discomfort, kidney problems, joint inflammation, and palpable purpura. In some instances, it may even lead to the development of thrombosis. An illustrative case involved a boy diagnosed with Henoch-Schönlein Purpura who experienced vein thrombosis in both legs. The patient experienced an improvement in his symptoms after receiving enoxaparin and colchicine.